An Assessment of Size Distribution of Rock Fragments from Blastin gin an Underground Hardrock Mine - F O. Otuonye (International Society of Explosives Engineers, 1985)
Full-face blasts were fired in a 12 x 8 ft drift of an underground hardrock mine in a basalt formation with porphyry copper to study the effects of drill pattern and explosive type on the size distribution of the resulting muckpile. Each muckpile produced by five full-face blasts was sampled four times with a scooptram equipped with a 5-cu yd bucket and the size distribution of the broken rock in each bucket was determined by screen analysis. Results show a strong dependence of the fragment size distribution of muckpile on the blast pattern and explosive type for a given rock type. The mean fragment size of the broken rock was compared with the predictive equations of other investigators. Random sampling of the muckpile from full-scale blasts and screen analyses of the samples are recommended in assessing the size distribution of the broken rock because of scaling errors that are inherent in full-scale blasts when designed from results of small-scale tests.